Post-operative retention of urine after general and spinal anesthesia in general surgical patients - Karki, Om Bahadur (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: Post-operative urinary retention (POUR) is an underestimated troublesome condition following surgery in which a patient cannot urinate even when the bladder is completely filled. with consequences like bladder dysfunction, urinary tract infection, and catheter-related complications. It is important to be aware and to identify patients at risk of developing POUR. The aim of the study was to determine the incidence and risk factors of POUR in general surgery patients.Methods: We conducted a prospective cohort study among 487 patients from January 2024 to April 2025. Ethical approval was obtained from the institutional review committee. Consecutive sampling method was used. The categorical variables were presented as frequencies, and were compared using the chi-squared test. Continuous variables were compared using the student's t test.  P-value of